Using Twitter to Enhance Secondaryschool Student's Vocabularyachievement - Uswatun Hasanah; Mirjam Anugerahwati (Graduate School of Universitas Negeri Malang, 2022)
Abstract: This paper examined the effectiveness of Twitter to enhance the students’ vocabulary achievement, because vocabulary is considered to have an important role in increasing students’ academic achievement and skills. It employed a quasi-experimental design and involved 64 students which divided into control and experimental group. The findings of the research discovered that both of group increased their achievement; however the students in experimental group get higher score than control group. The students in the control group were categorized as students with “good” achievement, while the students in the experimental were students with “very good” achievement.Abstrak: Artikel ini mengkaji efektivitas Twitter untuk meningkatkan prestasi kosakata siswa, karena kosakata dianggap memiliki peran penting dalam meningkatkan prestasi akademik dan keterampilan siswa. Metode yang digunakan adalah metode eksperimen semu dan melibatkan 64 siswa yang dibagi menjadi kelompok kontrol dan eksperimen. Hasil penelitian menemukan bahwa kedua kelompok mengalami peningkatan prestasi; namun siswa pada kelompok eksperimen mendapatkan skor rata-rata yang lebih tinggi daripada kelompok kontrol. Siswa pada kelompok kontrol dikategorikan sebagai siswa dengan prestasi “baik”, sedangkan siswa pada eksperimen adalah siswa dengan prestasi “sangat baik”.